Being for Death: the Ecstatic Time and Time Memory (Andamios, Revista de Investigación Social, 2014)
The fundamental concern analyzed in this paper is the question concerning a time that occidental philosophy as metaphysics has historically overlooked: the future. I start from looking at Heidegger’s analysis of temporality that the existential analysis of Dasein unveils and that he names “ecstatic time”, the time of Derrida’s différance as displacement and, finally, the time of psychic memory that Freud recognizes as après-coup, since all these three temporal phenomena are paradigmatic to think time as possibility besides presence.
Keywords: Ecstatic temporality; memory; Derrida’s phenomenology; Freudian psyche; dead